The Influence of Learning Environment on Students' Social Behavior - Renaldo, Nicholas; Widi, Rahma; Alkhairi, M. Habib; Hutahuruk, Marice Br; Veronica, Kristy (First Ciera Publisher, 2025)
This research is aim to analyze the influence of various learning environments (physical, digital, and hybrid) on students' social behavior. This research aims to contribute valuable insights into the evolving educational landscape, offering practical implications for educators, school administrators, and policymakers in fostering holistic student development. This study is grounded in Vygotsky's Sociocultural Theory, which emphasizes the fundamental role of social interaction in cognitive and behavioral development. This study employs a qualitative research design, using a phenomenological approach to explore students' lived experiences regarding the influence of the learning environment on their social behavior. This study demonstrates that students' social behavior is deeply influenced by the learning environment, whether traditional, digital, or hybrid. Well-structured and supportive learning environments, both physical and digital, promote positive social interactions, empathy, and teamwork among students. Future research should explore the long-term impact of different learning environments on students' social behavior, particularly in the context of evolving educational technologies.